Surface Modification of Nano-Sized Silicon Nitride with HFMA-MMA-VTMS Tercopolymer and their disperstion in FKM Composites - Wei, Qiang; Miao, Jibin; Cheng, Guojun; Qian, Jiasheng (Asian Journal of Chemistry, 2012)
In this work, a new macromolecular coupling agent HFMA-MMA-VTMS tercopolymer was synthesized using solution polymerization. The terpolymer's molecular structure was confirmed by FTIR and 1H NMR and GPC. The HFMA-MMA-VTMS tercopolymer was used for surface modification of silicon nitride (Si3N4) nanopowder. The structure surface properties and thermal stability of modified nano-Si3N4 were systematically investigated by FTIR, size distribution analyzer, TGA, TEM and nano-Si3N4/FKM composite was investigated by SEM. The results show that the macromolecular coupling agent bonds covalently on the surface of nano-sized Si3N4 particles and an organic coating layer was formed. The optimum loading of this macromolecular coupling agent HFMA-MMA-VTMS tercopolymer was 12 % (wt %) of nano-sized Si3N4. TEM also reveals that modified nano-Si3N4 possesses good dispersibility. SEM reveals that modified nano-Si3N4 dispersed more finely and homogeneously in the FKM matrix.